2004
DOI: 10.1002/lapl.200310033
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of silver nanoprisms into colloidal nanoparticles induced by femtosecond laser pulses

Abstract: Shape transformation of silver nanoprisms in aqueous solution was studied using femtosecond laser pulses. Irradiation of a pulsed Ti:Sapphire laser at 800 nm caused the shape change of the nanoprisms from triangle into sphere, forming a stable colloid of a narrow size distribution with the particle diameters having ∼10 nm. The effects of laser fluence on fragmentation and conversion were investigated using UV-vis absorption spectroscopy and transmission electron microscopy. The mechanism of laser-induced collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…3). We consider that as triangular silver nanoplates have been reported to decompose into colloidal nanoparticles by laser pulses 22, laser irradiation truncates the vertices of the triangular silver nanoplates to form nearly regular‐hexagonal and spherical silver nanoplates gradually. Compared with triangular nanoplates, the dipole resonance peaks of nearly regular‐hexagonal and spherical silver nanoplates are decreased due to the lack of sharp corners 5.…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…3). We consider that as triangular silver nanoplates have been reported to decompose into colloidal nanoparticles by laser pulses 22, laser irradiation truncates the vertices of the triangular silver nanoplates to form nearly regular‐hexagonal and spherical silver nanoplates gradually. Compared with triangular nanoplates, the dipole resonance peaks of nearly regular‐hexagonal and spherical silver nanoplates are decreased due to the lack of sharp corners 5.…”
Section: Resultscontrasting
confidence: 51%
“…Since the heating is very selective, the laser‐induced shape change of metal nanostructures provides simple means for post‐preparation shape control 11–17. Most of the early studies on the laser‐induced change of metal nanoparticles were concentrated on the size reduction of noble metal particles as a breaking‐down process to produce fine metal nanoparticles 18–22. We have recently reported that not only the mutual transposition of the core and the shell of a Au@Pt core/shell nanosphere but also the excavation of the silver core of a Ag@Pt nanoparticle can be obtained by exciting the surface plasmon resonances of platinum with picosecond laser pulses to form a new, reversed core/shell Pt@Au nanosphere 16 and a hollow platinum nanosphere 17, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In addition, laser pulses can be also used to fragment, reshape, and conjugate NPs. [10][11][12] Under carefully chosen experimental conditions, the stability of the obtained colloidal solutions can be very high, so that the NPs can be used for many applications in such fields as medicine, sensing, electronics, optics, and biophotonics. Colloidal gold NPs, for instance, are used for tumor-targeted drag delivery and cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3e and f), the plasmon band becomes very broad, which may originate from the overlap of different dipole resonances. 23 It is worth noting that the characteristic plasmon for the ID-GNPs occurs as well, but it extends to the near infrared region (Fig. 3c and d).…”
Section: Preparation and Characterization Of Id-gnpsmentioning
confidence: 95%